Homeless Street Youth: Personal Strengths and External Resources - Jing Zhang; Kate Fogarty (EDIS)
FCS2281, a 3-page fact sheet by Jing Zhang and Kate Fogarty, offers a fresh perspective on homeless youth. While these youth are often viewed as deviant and low in self-control, recent research finds that they have numerous strengths and efficiently use various resources to their advantage. The publication advocates taking a strengths-based (rather than problem-based) perspective when helping these youth. Published by the UF Department of Family, Youth and Community Sciences, October 2007.